2018
DOI: 10.3390/molecules23040963
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fusarium Mycotoxins in Cereals and Their Products—Metabolism, Occurrence, and Toxicity: An Updated Review

Abstract: Mycotoxins are secondary fungal metabolites, toxic to humans, animals and plants. Under the influence of various factors, mycotoxins may undergo modifications of their chemical structure. One of the methods of mycotoxin modification is a transformation occurring in plant cells or under the influence of fungal enzymes. This paper reviews the current knowledge on the natural occurrence of the most important trichothecenes and zearalenone in cereals/cereal products, their metabolism, and the potential toxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 182 publications
(201 reference statements)
0
67
1
1
Order By: Relevance
“…Of the major mycotoxins, HT-2 was not detected at all in the eastern region but was quantified only in 2% of the maize from the western region at 40.2 µg/kg concentration. Detection of HT-2 in the warm western region and not the cold eastern region as would be expected is contrary as it was reported that HT-2 was previously considered a problem in colder European climates [13]. Of the fumonisin Bs, FB1 occurred at the most frequency rate than FB2, FB3, and FB4.…”
Section: Distribution Of Fusarium (Free and Masked) Mycotoxins Acrosscontrasting
confidence: 58%
“…Of the major mycotoxins, HT-2 was not detected at all in the eastern region but was quantified only in 2% of the maize from the western region at 40.2 µg/kg concentration. Detection of HT-2 in the warm western region and not the cold eastern region as would be expected is contrary as it was reported that HT-2 was previously considered a problem in colder European climates [13]. Of the fumonisin Bs, FB1 occurred at the most frequency rate than FB2, FB3, and FB4.…”
Section: Distribution Of Fusarium (Free and Masked) Mycotoxins Acrosscontrasting
confidence: 58%
“…To our knowledge, no detailed review has focused on detoxification of mycotoxins through biotransformation though a series of reviews on the detoxification of certain mycotoxins have been published over the last 20 years [4,5,7,8,[13][14][15][16][17][18][19]. Furthermore, significant advances in the knowledge on detoxification of mycotoxins by biotransformation have been achieved recently.…”
Section: Key Contributionmentioning
confidence: 99%
“…Fusaric acid (FA, 19) was reduced to fusarinol (64), also called 5-butyl-2-pyridinemethanol, by the fungus Aspergillus tubingensis ( Figure S29) [59]. Fusarinol (64) was significantly less phytotoxic than fusaric acid (19). In fusarinol (64), the acid has been reduced to an alcohol group.…”
Section: Other Oxido-reductionsmentioning
confidence: 99%
See 2 more Smart Citations